A Rare Case of Acquired Fanconi's Syndrome With Monoclonal Gammopathy in an Infant. Issue 5 (29th October 2015) - Castillo, Brian; Chang, Brian N.; Wahed, Amer; Tholpady, Ashok
Abstract : Background: Monoclonal gammopathies associated with acquired Fanconi's syndrome (AFS) have been reported in the adult population. AFS is characterized by renal dysfunction resulting in proteinuria, aminoaciduria, hypophosphatemia, glucosuria, and hyperchloremic metabolic acidosis. In this case report, we document the clinical and laboratory findings of a preterm infant with features of both AFS and monoclonal gammopathy in the urine. Methods: Clinical suspicion of AFS prompted the following laboratory studies to be performed: urine protein electrophoresis (UPEP), urine immunofixation, and urine amino acid analysis with high performance liquid chromatography (HPLC). Results: Urine amino acid analysis revealed aminoaciduria. On UPEP, nonselective glomerular proteinuria was seen with a faint band in the gamma region. Urine immunofixation confirmed the presence of a monoclonal IgG lambda component with free monoclonal lambda light chains. Conclusion: To the best of our knowledge, this is the first case of pediatric AFS reported with a monoclonal gammopathy and monoclonal free light chains.